Distal Forearm Fracture Open Reduction–Internal Fixation: Sonographic Detection of Hardware Malalignment and Associated Tendon Injuries Missed by Radiography. (15th May 2017) - Morgan, Tara A.; Piper, Samantha L.; Lattanza, Lisa L.; Goldstein, Ruth B.; Link, Thomas; Motamedi, Daria
Abstract : Tendon injury is a known complication of distal radius fracture plate and screw fixation. Targeted musculoskeletal sonography is uniquely capable of assessing both tendon integrity and hardware abnormalities not recognized on radiographs. Each of the 3 patients described presented with pain after an open reduction–internal fixation following a distal forearm fracture. In each patient, radiographic findings, specifically the hardware position, were interpreted as normal. Important radiographically occult observations were subsequently made with sonography, including 3 proud screws and tendon injuries, all of which required surgical treatment. This case series demonstrates the clinical utility of musculoskeletal sonography in symptomatic patients after distal radius open reduction–internal fixation with negative radiographic findings. In our practice, sonography has been the most useful modality for precluding missing or delaying the diagnosis and treatment of these hardware complications. We advocate its use as an adjunct in any department performing musculoskeletal imaging.